Profitability and Correlation Between Koica Milk Shop and Dairy Farm in Selupu Rejang, Bengkulu, Indonesia - Soeng Chat Vichea; Endang Sulistyowati; Pao Srean (Badan Penerbitan Fakultas Pertanian (BPFP), 2020)
The objective of this research was to analyze profitability and correlation between KOICA milk shop and dairy farms in Selupu Rejang, Rejang Lebong, Bengkulu, Indonesia. Data driven were general condition, performance of Milk Shop, performance of dairy farms, and the correlation between KOICA milk shop and dairy farmer are evaluated. The methodology started by census that chosen only KOICA milk shop owner and dairy farmers who pooled the milk to KOICA milk shop. Data collected then tabulated and analyzed using Excel and Regression. The result showed that both KOICA milk shop and dairy all were gained properly benefit from dairy business. For the average, it was about IDR 6,557,057.75 per month equivalent to USD 493 as a profit in KOICA milk shop. The profit was depending on the milk production from dairy farmer only, if they couldn’t milk from dairy cow, KOICA milk shop won’t be able to earn money. The dairy farmers were also got IDR 3,620,311.09 (USD 272) per month as the average profit from milk, compost and calve. There was very high correlation between the milk produced by dairy farmers then processed by Koica Milk Shop and its profit was r : 0.99. The discovering of this research was very valuable information, and also important to whom it may concern in dairy business as well as dairy farmers and Government for applying or understanding to develop new strategies for reducing production costs and to increase the profit by using model of whom successful in dairy business.